Dual Substrate Specificity of the Rutinosidase from Aspergillus niger and the Role of Its Substrate Tunnel - Brodsky, Katerina; Kutý, Michal; Pelantová, Helena; Cvačka, Josef; Rebroš, Martin; Kotik, Michael; Kutá Smatanová, Ivana; Křen, Vladimír; Bojarová, Pavla (International journal of molecular sciences, 2020)
Rutinosidases (α-l-rhamnopyranosyl-(1-6)-β-d-glucopyranosidases, EC 3.2.1.168, CAZy GH5) are diglycosidases that cleave the glycosidic bond between the disaccharide rutinose and the respective aglycone. Similar to many retaining glycosidases, rutinosidases can also transfer the rutinosyl moiety onto acceptors with a free -OH group (so-called transglycosylation). The recombinant rutinosidase from Aspergillus niger (AnRut) is selectively produced in Pichia pastoris. It can catalyze transglycosylation reactions as an unpurified preparation directly from cultivation. This enzyme exhibits catalytic activity towards two substrates; in addition to rutinosidase activity, it also exhibits β-d-glucopyranosidase activity. As a result, new compounds are formed by β-glucosylation or rutinosylation of acceptors such as alcohols or strong inorganic nucleophiles (NaN3). Transglycosylation products with aliphatic aglycones are resistant towards cleavage by rutinosidase, therefore, their side hydrolysis does not occur, allowing higher transglycosylation yields. Fourteen compounds were synthesized by glucosylation or rutinosylation of selected acceptors. The products were isolated and structurally characterized. Interactions between the transglycosylation products and the recombinant AnRut were analyzed by molecular modeling. We revealed the role of a substrate tunnel in the structure of AnRut, which explained the unusual catalytic properties of this glycosidase and its specific transglycosylation potential. AnRut is attractive for biosynthetic applications, especially for the use of inexpensive substrates (rutin and isoquercitrin).
Keywords: simulace molekulového dockingu; substrátová specifita; rekombinantní proteiny; rutinosidase; disacharidy; fungální proteiny; Molecular Docking Simulation; glykosylace; Rutin; glykosidhydrolasy; Glycosylation; azide; Fungal Proteins; molecular modeling; glycosylation; tunnel; Glycoside Hydrolases; Catalytic Domain; Substrate Specificity; rutin; Disaccharides; Hydrolysis; Aspergillus niger; hydrolýza; katalytická doména; Recombinant Proteins